Dramaturgy in the making user's guide for theatre practitioners - Trencsényi, Katalin (London, United Kingdom Bloomsbury, 2015)
A thorough study of contemporary dramaturgical practices which draws on many examples from the work of leading theatre practitioners from the UK, Europe and North America. It maps the various ways in which a dramaturg may work in the theatre-making process and provides a theoretical framework to aid the reader in their own practice.
Institutional dramaturgy. Institutional dramaturgy: the beginnings -- Methods: curating -- Methods: dramaturgy and translation -- Methods: new drama development -- Production dramaturgy. Production dramaturgy: a theoretical overview -- Methods: product-led production dramaturgy -- Methods: process-led production dramaturgy -- Dance dramaturgy. Dance poetics: the history of dramaturgical thinking in dance -- Dance dramaturgy: the development of the role -- Methods: dance dramaturgs at work -- Conclusion: two things about dramaturgy.
Includes bibliographical references and index.
Keywords: Drama -- Technique; Playwriting